Soap! Soap! don't forget the soap! : an Appalachian folktale - Birdseye, Tom.; Glass, Andrew, 1949- (New York, NY : Holiday House, 1993)
A forgetful boy gets himself into trouble when he repeats what each person he meets on the road says to him.
Keywords: Folklore -- Appalachian Region